1999
DOI: 10.1002/(sici)1096-9926(199905)59:5<331::aid-tera4>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of select folate pathway genes, PAX3, and human T in a midwestern neural tube defect population

Abstract: Neural tube defects (NTDs) are a common birth defect, seen in approximately 1/1,000 births in the United States. NTDs are considered a complex trait where several genes, interacting with environmental factors, create the phenotype. Using a Midwestern NTD population consisting of probands, parents, and siblings from Iowa, Minnesota, and Nebraska, we analyzed a range of candidate genes, including 5,10-methylenetetrahydrofolate reductase (MTHFR), folate receptors-alpha (FOLR1; hereafter abbreviated "FR-alpha") an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…Analysis of the 326 population-based control children without NTDs identified a phenotypically normal child who possessed an amino acid substitution of serine to asparagine within exon 6 (corresponds to exon 7, Genbank U20391) of the FOLR1 gene. 85 Barber et al identified 4 unrelated NTD patients out of 50 with de novo missense mutations in exon 7 (Genbank U20391) and the 3 0 UTR of the FOLR1 gene, and one out of 150 control children with a gene conversion within the coding region using SSCP and Southern blot analysis. The authors reported that all 4 of the mutations in exon 7 and the 3 0 UTR affect the carboxy-terminal amino acid membrane tail, or the GPI anchor region of the receptor.…”
Section: Genetic Mutationsmentioning
confidence: 51%
See 1 more Smart Citation
“…Analysis of the 326 population-based control children without NTDs identified a phenotypically normal child who possessed an amino acid substitution of serine to asparagine within exon 6 (corresponds to exon 7, Genbank U20391) of the FOLR1 gene. 85 Barber et al identified 4 unrelated NTD patients out of 50 with de novo missense mutations in exon 7 (Genbank U20391) and the 3 0 UTR of the FOLR1 gene, and one out of 150 control children with a gene conversion within the coding region using SSCP and Southern blot analysis. The authors reported that all 4 of the mutations in exon 7 and the 3 0 UTR affect the carboxy-terminal amino acid membrane tail, or the GPI anchor region of the receptor.…”
Section: Genetic Mutationsmentioning
confidence: 51%
“…Trembath et al 85 detected a single de novo silent mutation in the sequence coding for the stop codon in exon 6 (TGA>TAA), which corresponds to exon 7 according to the nomenclature used in this review (Genbank U20391), out of a sample of 154 children affected with NTD compared to healthy control children in Iowa, Minnesota, and Nebraska using mutation detection enhancement gels. The authors postulated that the mutation, though silent, could interfere with effective stopping of translation, tying up or inhibiting protein release from the translational machinery.…”
Section: Genetic Mutationsmentioning
confidence: 99%
“…Some studies have reported an increased frequency of combined heterozygotes (MTHFR 677CT/1298AC) in NTD cases compared to controls (van der Put et al 1998;Richter et al 2001). Other studies, some with a relatively small sample size, show no association (Weisberg et al 1998;Stegmann et al 1999;Trembath et al 1999;Barber et al 2000;Volcik et al 2000). Only one study to date has shown a direct association of the 1298C allele with NTDs (De Marco et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…22 However, other investigations on the FRa gene suggest that it is unlikely to be a major factor influencing NTD risk. 23,24 Given its role in the folate uptake, RFC-1 genetic variants could represent another genetic risk factor for NTDs. A common polymorphism at position 80 in exon 2 of the RFC-1 gene has been identified.…”
Section: Introductionmentioning
confidence: 99%